2019
DOI: 10.1590/0102-311x00220217
|View full text |Cite
|
Sign up to set email alerts
|

Colaborações científicas em Zika: identificação dos principais grupos e pesquisadores através da análise de redes sociais

Abstract: Resumo: Devido à associação entre Zika e microcefalia, o Brasil recebeu atenção neste cenário. A situação de emergência exigiu rapidez e esforço coletivo dos pesquisadores de todo o mundo, e a Ciência se apressou nas investigações e publicação dos resultados. A partir das interações formadas, criou-se e se disseminou conhecimento científico. Publicações ainda são a melhor forma de divulgar o conhecimento científico. Através delas é possível registrar os progressos realizados em um campo de estudos e observar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Some studies have adopted bibliometric or scientometric perspectives, analysing papers and other documents to discuss aspects such as co-authorship, cooperative networks and the innovative potential of the ZVI topic [7][8][9][10]. In Maia et al [11], a first study on the scientific networks organized around ZVI and their most influential researchers used Social Network Analysis to map the co-authorship networks of Zika papers published in 2015/2016. The study showed that, besides the number of publications, the prominence of a given researcher in scientific networks can be explained by the diversity of partnerships and the establishment of connections with the pioneers in the field [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have adopted bibliometric or scientometric perspectives, analysing papers and other documents to discuss aspects such as co-authorship, cooperative networks and the innovative potential of the ZVI topic [7][8][9][10]. In Maia et al [11], a first study on the scientific networks organized around ZVI and their most influential researchers used Social Network Analysis to map the co-authorship networks of Zika papers published in 2015/2016. The study showed that, besides the number of publications, the prominence of a given researcher in scientific networks can be explained by the diversity of partnerships and the establishment of connections with the pioneers in the field [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Maia et al [11], a first study on the scientific networks organized around ZVI and their most influential researchers used Social Network Analysis to map the co-authorship networks of Zika papers published in 2015/2016. The study showed that, besides the number of publications, the prominence of a given researcher in scientific networks can be explained by the diversity of partnerships and the establishment of connections with the pioneers in the field [11]. Also, a recent study on Zika-related publications and patents from a scientometric perspective highlighted the strategic role played by the Latin America and Caribbean research network in terms of addressing the science and technology (S&T) challenges related to the outbreak [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bassani, Souza, Behr e Farias (2019) analisam as redes de publicações em programas de pós-graduação em Contabilidade, porém restringindo-se a áreas relacionadas à custos. Outros estudos se voltam às interações em um campo de pesquisa (Silva et al, 2006;Maia, Lenzi, Rabelo, & Oliveira, 2019…”
Section: Colaboração Científica Em Redes De Coautoriaunclassified
“…Nowadays, this approach has been used to analyze the triple arbovirosis outbreak caused by the Aedes aegypti mosquito (Zika-Dengue-Chikungunya) [14,15,17] and COVID-19, in Brazil and worldwide. The web system is available at <http://www.realm.net.br>.…”
Section: Experiments: Neglected Diseasesmentioning
confidence: 99%